A novel noninvasive diagnostic method for nonalcoholic steatohepatitis using two glycobiomarkers - Kamada, Yoshihiro; Ono, Masafumi; Hyogo, Hideyuki; Fujii, Hideki; Sumida, Yoshio; Mori, Kojiroh; Tanaka, Saiyu; Yamada, Makoto; Akita, Maaya; Mizutani, Kayo; Fujii, Hironobu; Yamamoto, Akiko; et al. (Hepatology (Baltimore, Md.), 2015)
Nonalcoholic fatty liver disease (NAFLD) is a growing medical problem; thus, discriminating nonalcoholic steatohepatitis (NASH) from NAFLD is of great clinical significance. For the diagnosis of NASH, liver biopsy‐proven histological examination is the current gold standard, and noninvasive and reliable biomarkers are greatly needed. Recently, we found that two glycobiomarkers, fucosylated haptoglobin (Fuc‐Hpt) and Mac‐2 binding protein (Mac2bp), are useful independently for NASH diagnosis. In this study, we confirmed that serum Fuc‐Hpt is suitable for the prediction of ballooning hepatocytes and that serum Mac2bp is suitable for the prediction of liver fibrosis severity in 124 biopsy‐proven NAFLD patients (training cohort). In addition, we found that the combination of serum Fuc‐Hpt and Mac2bp levels was an excellent tool for NASH diagnosis. Using receiver operating characteristic analyses, the area under the receiver operating characteristic curve, sensitivity, and specificity of the combination of these two glycobiomarkers were 0.854, 81.1%, and 79.3%, respectively. We established a prediction model for NASH diagnosis using logistic regression analysis: logit (p) = −2.700 + 0.00242 × Fuc‐Hpt + 1.225 × Mac2bp. To validate the prediction model, another 382 biopsy‐proven NAFLD patients were enrolled (validation cohort). In the validation cohort, the area under the receiver operating characteristic curve of this model for NASH diagnosis was 0.844, with 71.4% and 82.3% sensitivity and specificity, respectively. In addition, we investigated the significance of our developed NASH diagnosis model in ultrasound‐diagnosed NAFLD subjects who received medical health checkups (n = 803). Our model also could predict NAFLD disease severity in this larger population. Conclusion: The combination of serum Fuc‐Hpt and Mac2bp can distinguish NASH from NAFLD patients. Our noninvasive model using two serum glycobiomarkers contributes to a novel NASH diagnostic methodology that could replace liver biopsy. (Hepatology 2015;62:1433–1443)